Use of the Educaplay Educational Platform in the Literacy Process of Primary Education Students (ISCED Level 1) - Pesántez-Carmona, Elizabeth (2026)
This research was conducted in a public school located in the urban center of Cuenca, Ecuador, with primary school students (ISCED Level 1) who are experiencing difficulties in developing literacy skills. To address this problem, a pedagogical intervention was designed based on the Technological Pedagogical Content Knowledge (TPACK) model and the theoretical foundations of constructivism and constructionism, integrating the use of the Educaplay educational platform as a technological resource for developing interactive activities. The research adopts a mixed-methods approach and is structured using Sequential Transformative Design (DITRAS). Data collection included observations of classroom sessions with and without the use of technology, a survey administered to primary school teachers at the institution, and interviews with experts in the field of Language and Literature. The results show that the interactive activities designed in Educaplay significantly increased aspects such as attention, motivation, and academic performance of the students, especially with regard to phonological and syllabic skills and reading comprehension. In conclusion, the pedagogical intervention, based on the global-analytical approach and the development of linguistic awareness and reading comprehension in the early stages, combined with the appropriate use of interactive activities on the Educaplay platform, fosters meaningful, motivating, and autonomous learning in the initial phases of the reading process.